Crop2ML: An open-source multi-language modeling framework for the exchange and reuse of crop model components. (August 2021) - Midingoyi, Cyrille Ahmed; Pradal, Christophe; Enders, Andreas; Fumagalli, Davide; Raynal, Hélène; Donatelli, Marcello; Athanasiadis, Ioannis N.; Porter, Cheryl; Hoogenboom, Gerrit; Holzworth, Dean; Garcia, Frédérick; Thorburn, Peter; et al.
Abstract: Process-based crop models are popular tools to analyze and simulate the response of agricultural systems to weather, agronomic, or genetic factors. They are often developed in modeling platforms to ensure their future extension and to couple different crop models with a soil model and a crop management event scheduler. The intercomparison and improvement of crop simulation models is difficult due to the lack of efficient methods for exchanging biophysical processes between modeling platforms. We developed Crop2ML, a modeling framework that enables the description and the assembly of crop model components independently of the formalism of modeling platforms and the exchange of components between platforms. Crop2ML is based on a declarative architecture of modular model representation to describe the biophysical processes and their transformation to model components that conform to crop modeling platforms. Here, we present Crop2ML framework and describe the mechanisms of import and export between Crop2ML and modeling platforms. Highlights: An open framework is developed (Crop2ML) to support the development, exchange, and reuse of crop model components. Crop2ML provides a shared format to describe the specifications of model units and their composition. Crop2ML generates model components considering crop simulation platforms artifacts. Crop2ML model life cycle can be managed using a user-friendly JupyterLab interface. Crop2ML can be used to import and export model components into many different crop simulation platforms.